The Evolving Role of Sharia Supervisory Boards in a Volatile, Uncertain, Complex, and Ambiguous (VUCA) - Indiharwati, Arum (Journal of Economics, Business, and Government Challenges, 2024)
This paper examines the evolving role of Sharia Supervisory Boards (SSBs) in Islamic finance within a Volatile, Uncertain, Complex, and Ambiguous (VUCA) environment. Employing a systematic literature review (SLR) of 15 peer-reviewed articles published between 2009 and 2024 from reputable databases such as Scopus and SpringerLink, the study identifies key challenges SSBs face, including ensuring Sharia compliance amidst rapid technological advancements and dynamic regulatory landscapes. The findings highlight the importance of adaptability, interdisciplinary expertise, and enhanced collaboration in enabling effective governance. SSBs are urged to transition from traditional compliance-focused roles to adaptive governance frameworks capable of addressing the complexities of contemporary financial systems. The study contributes to the existing literature by offering a comprehensive analysis of SSB adaptability in the VUCA era and providing actionable recommendations for policymakers and financial institutions, such as strengthening SSB autonomy, fostering member proficiency, and encouraging cross-border collaboration to address global uncertainties.